A second chance for yesterday - Sinn, R. A. (Solaris, 2023)
"Nev Bourne is a hotshot programmer for the latest and greatest tech invention out there: SavePoint, the brain implant that rewinds the seconds of all our most embarrassing moments. She's been working non-stop on the next rollout, even blowing off her boyfriend, her best friend and her family to make SavePoint 2.0. But when she hits go on the test-run, she wakes up the next day only to discover it's yesterday. She's falling backwards in time, one day at a time. As things spiral out of control, a long-lost friend from college reappears in her life claiming they know how to save her. Airin is charming and mysterious, and somehow knows Nev intimately well. Desperate and intrigued, Nev takes a leap of faith. A friendship born of fear slowly becomes a bond of deepest trust, and possibly love. With time running out, and the whole world of SavePoint users at stake, Nev must learn what it will take to set things right, and what it will cost"--